2024
DOI: 10.3390/en17030630
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning-Based Electricity Consumption Forecast and Management System for Renewable Energy Communities

Miguel Matos,
João Almeida,
Pedro Gonçalves
et al.

Abstract: The energy sector is currently undergoing a significant shift, driven by the growing integration of renewable energy sources and the decentralization of electricity markets, which are now extending into local communities. This transformation highlights the pivotal role of prosumers within these markets, and as a result, the concept of Renewable Energy Communities is gaining traction, empowering their members to curtail reliance on non-renewable energy sources by facilitating local energy generation, storage, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Bekdaş et al [10] utilized five foundational regression algorithms and five ensemble algorithms to predict cooling loads (the amount of energy that must be removed from or consumed in a space to keep its temperature at an acceptable level or within an acceptable range) based on the basic architectural and structural characteristics of low-rise buildings in the tropics and found that the Histogram Gradient Boosting algorithm and stacking models efficiently modeled the relationship between the predictors and cooling load. Matos et al [11] suggested a method to manage community energy balance through electricity consumption forecasts via eXtreme Gradient Boosting (XGBoost) and used a decision algorithm for energy trading with the public grid based on solar production and energy consumption forecasts, storage levels, and market electricity prices. Son et al [12] suggested an algorithm for short-and medium-term electricity consumption forecasts by combining the Gated Recurrent Unit (GRU) model (which achieves accurate long-term forecasts) with the Prophet model (which is appropriate for modeling seasonal events), and their proposed model reduced forecasting errors and provided insights into electricity consumption patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Bekdaş et al [10] utilized five foundational regression algorithms and five ensemble algorithms to predict cooling loads (the amount of energy that must be removed from or consumed in a space to keep its temperature at an acceptable level or within an acceptable range) based on the basic architectural and structural characteristics of low-rise buildings in the tropics and found that the Histogram Gradient Boosting algorithm and stacking models efficiently modeled the relationship between the predictors and cooling load. Matos et al [11] suggested a method to manage community energy balance through electricity consumption forecasts via eXtreme Gradient Boosting (XGBoost) and used a decision algorithm for energy trading with the public grid based on solar production and energy consumption forecasts, storage levels, and market electricity prices. Son et al [12] suggested an algorithm for short-and medium-term electricity consumption forecasts by combining the Gated Recurrent Unit (GRU) model (which achieves accurate long-term forecasts) with the Prophet model (which is appropriate for modeling seasonal events), and their proposed model reduced forecasting errors and provided insights into electricity consumption patterns.…”
Section: Introductionmentioning
confidence: 99%